2014
DOI: 10.1637/10855-043014-case.1
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringensType A Enteritis in Blue and Yellow Macaw (Ara ararauna)

Abstract: This study describes an outbreak of necrotic enteritis caused by Clostridium perfringens type A in captive macaws (Ara ararauna). Two psittacine birds presented a history of prostration and died 18 hr after manifestation of clinical signs. The necropsy findings and histopathologic lesions were indicative of necrotic enteritis. Microbiologic assays resulted in the growth of large gram-positive bacilli that were identified as C. perfringens. PCR was used to identify clostridium toxinotypes and confirmed the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…C. perfringens has been linked to enteritis in multiple mammal and bird species [34,39,[41][42][43][44], including in lorikeets and other psittacines [5,32,33,[45][46][47]. In this study, young lorikeets (< 2 years old) were more likely to develop clostridial enteritis.…”
Section: Demographics Of Lorikeet Enteritismentioning
confidence: 74%
See 2 more Smart Citations
“…C. perfringens has been linked to enteritis in multiple mammal and bird species [34,39,[41][42][43][44], including in lorikeets and other psittacines [5,32,33,[45][46][47]. In this study, young lorikeets (< 2 years old) were more likely to develop clostridial enteritis.…”
Section: Demographics Of Lorikeet Enteritismentioning
confidence: 74%
“…While several clostridial species are considered normal flora in some avian species including poultry, in psittacines, clostridial species are rarely found in the intestines of healthy birds, and taxa such as C. colinum and C. perfringens are considered pathogenic [4,31,59,68,69]. Previous studies have linked the C. perfringens beta-2 toxin (cpb2) identified in CZA birds with enteritis in psittacines [33], storks [70], pigs [71], and poultry [72]; however, the cpb2 toxin has also been identified in healthy individuals (poultry, horses, dogs, and other avian species) and its role enteritis is not clear [73][74][75][76][77]. C. colinum-linked enteritis has only been reported in avian species, but virulence factors, toxins, and disease pathogenesis for C. colinum have yet to be fully elucidated [59].…”
Section: Lorikeet Enteritis: Microbes To Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…There are increasing reports of clostridial diseases in wild or captive wild birds, with Tyzzer's disease (Clostridium piliforme) (4,5), ulcerative enteritis/quail disease (C. colinum) (6), C. tertium-associated enteritis plus C. perfringens-associated enteritis (7,8) and necrotic enterocolitis (9) being identified in lorikeet or lory species. Two sources have recognized a novel disease within rainbow lorikeets (Trichoglossus haematodus haematodus) (10) and red-flanked lorikeets (Chamorsyna placentis) (11), characterized macroscopically by thickened crops with nodular-to-diffuse mucosal nodules and gas-filled bubbles, and histologically as emphysematous ingluvitis.…”
Section: Introductionmentioning
confidence: 99%
“…16 Our knowledge about C. perfringens-associated enteritis in exotic birds is limited. 2,3,5,6,10,12 It has previously been suggested that this microorganism may cause a NE-like disease in both free-ranging and captive lorikeets. 6,10 Between 2000 and 2018, 24 of the 67 (36%) lorikeets necropsied at the Institute of Animal Pathology of the University of Bern were diagnosed with NE-like disease, which represented the most frequent diagnosis.…”
mentioning
confidence: 99%